Design of a rainstorm over the Saffron Valley Basin and runoff modeling using techniques Modern geography - WALY FRIH Al-Rikabi, Nasser; Obaid Kazem Al-Masoudi , Farakid (Journal of College of Education, 2021)
This study aims to use modern technology, including geographic information systems technology, to reveal the formal characteristics of the Wadi Saffron basin, represented by the spatial, longitudinal, morphological and topographical characteristics, and the characteristics of the drainage network. , In order to build a geographic information base for the basin, and the DEM satellite imagery was used to map the drainage network in Wadi Al-Zafaran, and these maps were entered into Arc GIS 10.7. A map of the river basin and the water network was produced, classified according to the method of introduction and application of valley analysis within Arc GIS and mapping software. Digital elevations and contour lines of the study area. Digital maps were produced and various linear measurements were taken and some spatial relationships were made between the various features of the basin. The natural characteristics that affect the basin were also studied, especially the rocky nature, climatic and topographical characteristics. The total area of ​​the basin was (612.4 km2), and a topographic model was drawn that reflects its topographical characteristics and the extent of its impact on the characteristics of the river network. Therefore, the adoption of new technologies played a role in knowledge. The precise details of the study area without resorting to the field study as rainstorms (modeling) after designing a rainstorm, and its intensity varies and shows the correlation of flood waves, modeling and simulation with realistic data with the intensity of rain. This was done using recent software, including the 10.1W (watershed) watershed model program, the WMS10.1 program (HYDROCAD (HEC-HMS)) to find rainfall intensity and its relationship to surface runoff in the Dwerig Basin, and the Surfer 13 program and system. Geographic Information - ARC10. Scene 7 and QGIS 3.8 geo-modeling program.